Development Of Species-Specific Microsatellite Markers Of Termite Globitermes Sulphurues Haviland (Blattodea: Termitidae) For Genetic Population Analysis By Using Next-Generation Sequencing (Ngs) Approach - Khizam, Nur Aizatul Nathasha (2019)
Subterranean termite Globitermes sulphureus (higher termite) comprise a wide distributed family of termites, found throughout the tropical regions of the world. Little is known about G. sulphureus role in biology, dispersal range, and their control due to lack of research to gather molecular data information. Hence, from the availability of whole sequences of G. sulphureus, a great opportunity to develop species-specific microsatellite markers can be done. In this study, a total of 243,057 transcripts were generated from transcriptome dataset of G. sulphureus, with dinucleotide repeats being the most abundant. From these, a total of new 30 species-specific microsatellite markers were designed using next-generation sequencing (NGS) procedures. All of 30 markers were successfully amplified and showed visible scorable polymorphism. The polymorphic information content (PIC) values showed greater than 0.5 in which proved that all markers here had high level of polymorphism, with 3 to 9 alleles per locus were identified. The observed and expected heterozygosities ranged from 0 to 0.83 and 0 to 0.98, respectively. The species-specific microsatellites developed in this study can be used to inferred genetic diversity, breeding pattern and population genetic structure of G. sulphureus. In addition, the breeding pattern, genetic diversity and population genetic structure of G. sulphureus remain poorly understood.